Career calling: women STEM graduates in the United Arab Emirates. Issue 2 (20th August 2020) - Kemp, Linzi J.; Ahmad, Norita; Pappalardo, Lucia; Williams, Alison
Abstract : Purpose: The purpose of this study is to investigate career choices by female graduates from science, technology, engineering and mathematics (STEM) to determine factors that influenced their entry, abandonment or persistence of STEM careers. Design/methodology/approach: Life history narratives were collected from a sample group of employed citizens and expatriate women (all STEM graduates) in the United Arab Emirates (UAE). Content of interview transcripts was analyzed for emergent themes of influence on these participants career decisions. Findings: Four significant themes of calling were found: gift of intellect, belief in a faith, shared community and meaning of work. A typology of calling was constructed to reflect these themes influences on the entry, abandonment or persistence of women in a STEM career. Research limitations/implications: The results of this study were from a small sample of women in a particular country. The implication is to extend this study to a larger number of participants and to other countries to generalize the results. Practical implications: Insight into career decisions of female STEM graduates impacts on employee recruitment and retention policies within those professions. Originality/value: Research originality is evident, to the best of the authors' knowledge, as this is the first study to explore the influence of calling for careers of STEM women working in the Middle East North Africa region.